Safety and pharmacokinetic profile of rufinamide in pediatric patients aged less than 4 years with Lennox-Gastaut syndrome: An interim analysis from a multicenter, randomized, active-controlled, open-label study. (May 2016) - Arzimanoglou, Alexis; Ferreira, Jose A.; Satlin, Andrew; Mendes, Shannon; Williams, Betsy; Critchley, David; Schuck, Edgar; Hussein, Ziad; Kumar, Dinesh; Dhadda, Shobha; Bibbiani, Francesco
Abstract: Objective: A good knowledge of safety and age group-specific pharmacokinetics (PK) of antiepileptic drugs (AEDs) in young pediatric patients is of great importance in clinical practice. This paper presents 6-month interim safety and PK from an ongoing 2-year open-label study (Study 303) of adjunctive rufinamide treatment in pediatric subjects ≥1 to <4 years with inadequately controlled epilepsies of the Lennox-Gastaut syndrome (LGS) spectrum. Methods: Subjects ( N = 37) were randomized to either rufinamide or any other approved AED chosen by the investigator as adjunctive therapy to the subject's existing regimen of 1–3 AEDs. Results: Interim safety results showed that treatment-emergent adverse events (TEAEs) were similar between the rufinamide (22 [88.0%]) and any-other-AED group (9 [81.8%]), with most events considered mild or moderate. A population PK analysis was conducted including plasma rufinamide concentrations from Study 303 and two other study populations of LGS subjects ≥4 years. The rufinamide PK profile was dose independent. The apparent clearance (CL/F) estimated from the PK model was 2.19 L/h; it was found to increase significantly as a function of body weight. Coadministration of valproic acid significantly decreased rufinamide CL/F. CL/F was not significantly affected by other concomitant AEDs, age, gender, race, hepatic function, or renal function. No adjustments to body weight-based rufinamide dosing in subjects ≥1 to <4 years are necessary. Significance: Rufinamide was safe and well tolerated in these pediatric subjects. Results from the interim analysis demonstrate that rufinamide's safety and PK profile is comparable in subjects ≥1 to <4 and ≥4 years with LGS. Clinical Trial Registration: Study 303 (clinicaltrials.gov:NCT01405053 ). Highlights: Study 303 features an active comparator arm with investigator-chosen add-on AEDs. Rufinamide was safe and well tolerated in pediatric subjects ≥1 to <4 y of age. Rufinamide PK in subjects ≥1 to <4 y comparable to prior analyses in LGS subjects ≥4 y. No adjustments necessary to weight-based dosing for rufinamide in patients ≥1 to <4 y.